Analisis Penyajian Soal Latihan Pelafalan Bahasa Mandarin dalam Buku Elementary Comprehensive Course I - Yuk Ting (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2020)
Pronunciation is the entrance to speaking skills. The presentation of structured and planned teaching materials will greatly help language learners in mastering pronunciation techniques. There are many textbooks that provide creative and interesting pronunciation practice questions, but they do not pay attention to the importance of regularity and the correct stages of presentation.The Elementary Comprehensive Course I (???????? (I) F?zh?n Hàny? Ch?jí Z?nghé (I) textbook) is one of the books published by the PRC which is also widely used by Mandarin students in Indonesia. In the book series for the beginner level there are similarities in layout, namely pronunciation practice questions, new vocabulary lists, texts / discourses, practice questions to strengthen understanding of texts / discourses. The focus of this research is on the part of pronunciation practice questions. In it, there are various forms of practice questions aimed at strengthening pronunciation mastery, but many users of this book still complain about the difficulty of mastering Mandarin pronunciation. What is the reason? This study will describe the questions contained in the Elementary Comprehensive Course I textbook, then identify the accuracy in the presentation of existing practice questions, based on the principles of presenting the practice questions from ??? (Zhào J?nmíng).